Volume 1: Turbomachinery 1988
DOI: 10.1115/88-gt-83
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-3D Solutions for Transonic, Inviscid Flows by Adapative Triangulation

Abstract: This paper describes an algorithm for computing two-dimensional transonic, inviscid flows. The solution procedure uses an explicit Runge-Kutta time marching, finite volume scheme. The computational grid is an irregular triangulation. The algorithm can be applied to arbitrary two-dimensional geometries. When used for analyzing flows in blade rows, terms representing the effects of changes in streamsheet thickness and radius, and the effects of rotation, are included. The solution is begun on a coarse grid, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…A systematic study to calculate forced response levels in a fan and a turbine and compare results with corresponding measured data was reported by Chiang and Kielb (1992). Row defects due to wake disturbances were modelled with a "semi-empirical rotor wake/vortex model" due to Maijigi and Gliebe (1984) and "measured data for inlet distortion and a quasi-3D Euler code" due to Holmes et al (1988) to represent pressure disturbances. Several references are cited in the paper and may be studied to examine how wake data, empirical models and CFD approaches have been used by several researchers to compute forcing functions.…”
Section: Aerodynamic Analysesmentioning
confidence: 99%
“…A systematic study to calculate forced response levels in a fan and a turbine and compare results with corresponding measured data was reported by Chiang and Kielb (1992). Row defects due to wake disturbances were modelled with a "semi-empirical rotor wake/vortex model" due to Maijigi and Gliebe (1984) and "measured data for inlet distortion and a quasi-3D Euler code" due to Holmes et al (1988) to represent pressure disturbances. Several references are cited in the paper and may be studied to examine how wake data, empirical models and CFD approaches have been used by several researchers to compute forcing functions.…”
Section: Aerodynamic Analysesmentioning
confidence: 99%
“…To improve the prediction of discontinuities such as shocks and slip lines, a Q3D Euler solver EULQ3D3 was developed using adaptive grids. The first version of EULQ3D3 solves the Euler equations on structured grids (Berger and Oliger, 1984;Bonomi, 1987;Fritts, 1988), the second version uses unstructured triangle grids (Holmes et al, 1983;Holmes, 1989).…”
Section: Improvement Of the Shock Capturing (Eulq3d3)mentioning
confidence: 99%
“…To avoid the disadvantages noted above, a new version of the Euler code EULQ3D3 was written, which uses unstructured adaptive grids with triangles (Holmes et al, 1983;Holmes, 1989). With such grids high-gradient flow regions can be refined by introducing additional grid cells without affecting the other flow regions.…”
Section: Eulq3d3 For Unstructered Gridsmentioning
confidence: 99%
“…In three dimensions, published work to date has been restricted to inviscid flows around external aerodynamic configurations (see Bristeau et al (1985), Jameson et al (1987) and Peraire et al (1988) for good examples) and has demonstrated a very impressive degree of flexibility. Application to turbmachinery flows has lagged behind and so far has been limited to two dimensions (see Holmes et al (1988) for inviscid flow and Siden et al (1989) and Hwang et al (1990) for viscous flow).…”
Section: Introductionmentioning
confidence: 99%